A structured, home-based exercise programme in kidney transplant recipients (ECSERT): A randomised controlled feasibility study - Roseanne E. Billany; Jamie H. Macdonald; Stephanie Burns; Rafhi Chowdhury; Ella C. Ford; Zahra Mubaarak; Gurneet K. Sohansoha; Noemi Vadaszy; Hannah M. L. Young; Nicolette C. Bishop; Alice C. Smith; Matthew P. M. Graham-Brown (PLoS ONE, 2025)
Background Cardiometabolic diseases are a major cause of morbidity and mortality in kidney transplant recipients (KTR) due to clustering of traditional and non-traditional risk factors including poor physical fitness and physical inactivity. Exercise may mitigate the risk of these diseases in this population but evidence is limited, and physical activity levels are low. The ECSERT randomised controlled trial assessed the feasibility of delivering a structured, home-based exercise intervention in KTR at increased cardiometabolic risk. Methods Fifty KTR (>1-year post-transplant) were randomised 1:1 to: intervention (INT: a 12-week home-based combined aerobic and resistance exercise programme) or control (CTR: guideline-directed care). The a-priori thresholds for feasibility were: recruitment of 20% of eligible participants (≥2 participants per month); adherence (an average of ≥ 3 exercise sessions per week); and attrition (≤30%). Results One hundred and seventy-one patients were screened and 94 (55%) were eligible and invited to take part in the study. Fifty of those invited (53%) were recruited across 22 months of recruitment. Consented participant characteristics were: age 50 ± 14 years (INT 49 ± 13; CTR 51 ± 15), 23 male (INT 10; CTR 13), eGFR 59 ± 19 ml/min/1.73m2 (INT 60 ± 20; CTR 61 ± 21), 35 White British (WB), 13 South Asian (SA), 1 Caribbean, and 1 Mixed ethnicity (INT 17 WB, 7 SA, 1 Mixed; CTR 18 WB, 6 SA, 1 Caribbean). Intervention participants (n = 22 completed) recorded an average of 4.4 ± 1.4 exercise sessions per week (aerobic 2.8 ± 1.1; strength 1.6 ± 0.5). Three participants withdrew from the intervention group (1 COVID-19 infection, 1 recurrent urine infections unrelated to the trial, 1 time/family circumstances) and one from the control group (lost to follow-up; 8% attrition). There were no serious adverse events reported. Conclusion Despite previous evidence showing physical fitness and activity levels are low in KTR, the present results support that a structured, home-based exercise programme is feasible in this population. Specifically, a-priory recruitment, adherence, and retention thresholds were all exceeded. The groups were well matched and there was encouraging representation of female participants and participants from a non-white background. Thus, this study supports further development and testing of home-based programmes of exercise and activity for KTR. Trial registration ClinicalTrials.gov NCT04123951